Explosiveness: Territories of war and technoscientific practices in Colombia. - Pardo Pedraza, Diana; Morales Fontanilla, Julia (Journal of Latin American & Caribbean Anthropology, 2023)
La Serranía de la Macarena has been a crucial scenario in the Colombian war. In this region, the army and FARC‐EP guerrillas widely deployed aerial bombardment and improvised landmines to control the territory and contain their adversaries. This article is a collaborative ethnographic exploration of retazos—snippets of material‐discursive practices we collected in our fieldworks: a demining project and a state morgue. What can explosive military technologies and their aftermath tell us about the place of war in Colombia? Through two ethnographic retazos, we account of how forensic workers and mine‐removal experts engage with the material traces of explosives and produce bodies and landscapes as territories of war. We reflect on these topographies through the concept of explosiveness. Understood as a tendency, a condition, and a field of forces, explosiveness offers a distinct point of entry to reflect on the material and affective aftermath of landmines and bombs.